IMPLEMENTATION OF THE DEMOCRATIC SYSTEM OF ELECTING LASNGSUN REGIONAL HEADS OF REGENTS AND DEPUTY REGENTS IN BIMA REGENCY - Junaidin; Otom Mustomi (Adisam Publisher, 2024)
The implementation of the Democratic System of Direct Election of Regional Heads of Regents and Vice Regents in Bima Regency in this writing consists of variables. Purpose of Writing, To find out the implementation of the local democratic system in the process of direct election of the Regent and Vice Regent of Bima. To find out and analyze the influence of candidates from political party cadres who carry the votes for the Bima Regency Regent election. To find out the influence of prospective spouses from Public Figures who are not from political cadres carried by the party on the election of the Regent of Bima Regency. Research Method is using qualitative research methods that are normative, the results of Democratic Research are ideas or views of life that prioritize equal rights and obligations and equal treatment for all citizens without exception are truly noble ideals. In some basic needs and needs, all human beings are